Trouble in the Psychosphere: HBO’s True Detective (2014) as a Hybrid Genre. - Lopes, Elisabete (2020)
Submitted by Marta Frade (marta.diogo@ess.ips.pt) on 2020-12-04T16:06:33Z No. of bitstreams: 1 Elisabete Lopes -Trouble in the Psychosphere.pdf: 457347 bytes, checksum: 2e570c7fb926097b2b759bfa90804fe0 (MD5)